Keragaan Tanaman Kacang Tanah Pasca Serangan Hama Kutu Kebul Bemisia Tabaci Genn - Sari, Kurnia Paramita; Aini, Nurul; Rahardjo, Bambang Tri (Proceedings Series on Physical & Formal Sciences, 2021)
Peanut is one of the plants that are widely cultivated by farmers. Biotic and abiotic stresses are one of the barriers to peanut productivity. The biotic attack of the whitefly Bemisia tabaci infestation on peanuts impacts the performance of the plant itself. The purpose of this study was to determine the performance of peanut plants after being attacked by whiteflies.The research was carried out in 2019 using 10 peanut genotypes arranged according to a completely randomized design and repeated three times. The research plants were infested with whitefly and then observed several characters, including the number of flowers, number of gynophores, number of branches, number of roots, root length, plant height, number and weight of pods, number and weight of seeds, and crop yield index. The results showed that the groundnut infested with whitefly contained sooty dew as a direct insect attack. The population and sooty dew caused the number of flowers and branches to be low, the value of the number of dry pods and dry pod weight was low, the dry seed weight was low, and the crop harvest index was also low.